Why Consumers Stay Loyal: The Interplay of Brand Experience, Brand Personality, Perceived Value, and e-WOM in Local Skin Care Markets - Chiquita Maharani (The Eastasouth Management and Business, 2026)
This study examines the influence of brand experience, brand personality, perceived value, and electronic word of mouth on consumer loyalty toward local skin care products in West Java. A quantitative research design was employed using a survey method with 150 respondents who had experience using local skin care brands. Data were collected through a structured questionnaire measured using a five-point Likert scale and analyzed using SPSS version 25. Multiple linear regression analysis was applied to test the proposed hypotheses. The results indicate that brand experience, brand personality, perceived value, and electronic word of mouth all have positive and significant effects on consumer loyalty. Among these variables, perceived value emerges as the strongest predictor of loyalty, followed by brand experience, brand personality, and electronic word of mouth. These findings suggest that consumers’ loyalty to local skin care brands is shaped not only by functional benefits but also by emotional experiences, symbolic brand characteristics, and digital communication dynamics. The study provides empirical insights for local skin care brands in designing effective marketing strategies to strengthen long-term consumer loyalty and enhance competitiveness in an increasingly dynamic market.